ປຽບທຽບຜົນຜະລິດຂອງເຫັດນາງລົມ ໂດຍໃຊ້ວັດສະດຸທີ່ແຕກຕ່າງກັນ - PHOMLASABOUD, Khantavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
The research to studied of different substratematerial for improve the high yield and economic of oyster mushroom. This study were start on 6 month at department of agronomy science, faculty of agriculture, Souphanouvong University. The research used the Randomized Complete Block Design (RCBD) has 4 rap 5 materials such as sawdust, Rice straw, Dried teak leave ,Dried banana stem and Dried water hyacinth. For each sample have 50 bags on oyster mushroom fungus to compare on the yield components of mushroom. For five materials cold improve the oyster mushroom yield from T2 the straw more than other and straw was suitable and positive significant on 99% at 235.75 g per bag and, dry trunk of banana tree T1 at 169.25, T4 at 166.75, T3 at 137.25 and T5 at 75.42 g per bag. However, the straw has to improve the high yield of oyster mushroom In this research and the short time on the 6 month next time recommendation should have more time such as test on the rainy season and dry season for standard trial in the one year.